1989
DOI: 10.4141/cjss89-080
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antecedent Freeze-Thaw Frequency on Runoff and Soil Loss From Frozen Soil With and Without Subsoil Compaction and Ground Cover

Abstract: Fig. 2. The coefficient of determination (r') was 0.82 and, as indicated, residual dispersion was independent of runoff volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The work by Edwards and Burney (1989) clearly showed the experimental difficulties associated with this general subject area. After thawing, continuously frozen soil profiles gave much greater sediment and runoff values than the equivalent profiles subjected to alternate freeze/thaw cycles.…”
Section: Effects Of Freezing On Individual Physical Characteristimentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Edwards and Burney (1989) clearly showed the experimental difficulties associated with this general subject area. After thawing, continuously frozen soil profiles gave much greater sediment and runoff values than the equivalent profiles subjected to alternate freeze/thaw cycles.…”
Section: Effects Of Freezing On Individual Physical Characteristimentioning
confidence: 99%
“…With time and conditions favoring evaporation and drainage, soil strength and erosion resistance increase (Formanek et al, 1983). Edwards and Burney (1989) compared the extent of soil loss and runoff from freeze/thaw soil with and without subsoil compaction and ground cover. Soil compaction resulted in a 45% increase in sediment loss, compared with that from noncompacted controls.…”
Section: Effects Of Freezing On Individual Physical Characteristimentioning
confidence: 99%
“…In early spring, partially melted frozen soils are subject to accelerated water erosion. In the United States, about 4.2 million km^ of agricultural lands are affected by soil freezing and thawing (Formanek et al, 1984), with similar problems reported in Norway, Canada, and Japan (Edwards and Burney, 1989;Lundekvam and Skoien, 1998;Mizoguchi and Yabukl, 2002).…”
Section: Noriyuki Kamachi Hiromi Imoto Masaru Mizoguchi Tsuyoshi Miyamentioning
confidence: 89%
“…Winter rye was seeded manually and lightly incorporated using a "weasel" tiller. The physical characteristics of this soil are described in a previous publication (Edwards and Burney 1989). The flow concentration portion of the original soil cassette was redesigned ( Fig.…”
Section: Methodsmentioning
confidence: 99%